2021
DOI: 10.1503/cmaj.210131
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating and mitigating the evolving impacts of COVID-19 on ethnocultural communities: a participatory action mixed-methods study

Abstract: Mahatma Gandhi observed that "the true measure of any society can be found in how it treats its most vulnerable members." Ethnocultural communities, defined by their unique shared characteristics (e.g., cultural traditions, language, country of origin), 1 face greater challenges and have higher rates of poverty and illness than the general Canadian population. Migration results in conditions that affect all social determinants of health and disproportionally affect health outcomes, herein referred to as vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…This study provides a better understanding of the pandemic and lockdown experience of migrant adolescents in Switzerland and confirms some of our initial hypotheses. Furthermore, our results regarding the challenges this population may face are in line with other studies carried out at the time of the pandemic among young migrants arriving in high-income countries (Nakhaie et al , 2022; Couch et al , 2021; Campbell-Scherer et al , 2021; Ahmed et al , 2021; Clarke et al , 2021; Kellock and Ntalianis, 2020; Gautham et al , 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study provides a better understanding of the pandemic and lockdown experience of migrant adolescents in Switzerland and confirms some of our initial hypotheses. Furthermore, our results regarding the challenges this population may face are in line with other studies carried out at the time of the pandemic among young migrants arriving in high-income countries (Nakhaie et al , 2022; Couch et al , 2021; Campbell-Scherer et al , 2021; Ahmed et al , 2021; Clarke et al , 2021; Kellock and Ntalianis, 2020; Gautham et al , 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, we note that there were gaps in the access to information and in the understanding of the sanitary measures and the virus itself. This finding has also been observed by other authors who point misinformation in migrant communities linked to language barriers and possible cultural distance from the information given (Campbell-Scherer et al , 2021; Ahmed et al , 2021). In another study conducted in Switzerland (Ruedin et al , 2022), it was shown that despite language barriers, surveyed migrants were able to obtain information about the virus, notably from data available in their country of origin.…”
Section: Discussionsupporting
confidence: 87%
“…Further, negative experiences due to racism or discrimination increase institutional mistrustincluding the health system, government, employers, and unions (41)(42)(43)(44). For example, due to the notoriety associated with various large COVID-19 outbreaks in meat processing facilities, migrant workers reported experiencing discrimination and being stigmatized as sources of community COVID-19 transmission (45).…”
Section: Disproportionately High Covid-19 Infection Hospitalization A...mentioning
confidence: 99%
“…Migrant workers may have misperceptions about COVID-19 and receive inaccurate health information from informal networks, especially if public health or occupational health and safety materials are not culturally tailored or translated into primary languages (42,44,49,50). Culturally tailored health information may include information delivered by trusted community leaders or that considers culture and religion-specific concerns (i.e., Ramadan or Lent) (50).…”
Section: Disproportionately High Covid-19 Infection Hospitalization A...mentioning
confidence: 99%
“…The pandemic has widened previously existing economic and health disparities, causing proper healthcare and diabetes management practices to become less attainable by patients of lower SES [ 14 ]. One study found that poverty level was associated with higher rates of hospitalization and death [ 15 ].…”
Section: Reviewmentioning
confidence: 99%